Factors Associated with Breast Cancer in Women of Reproductive Age at Dr. Pirngadi Hospital, Medan, North Sumatera - Sari, Mila Trisna; Sarumpaet, Sorimuda; Siregar, Fazidah Aguslina (Journal of Maternal and Child Health, 2021)
Background: Breast cancer has the highest prevalence in Indonesia. The objective of the research was to analyze the risk factors which influenced the incidence of breast cancer in women of reproductive age.Subjects and Method: This was a case-control study conducted at Dr. Pirngadi Hos